Esthetic outcome for implant therapy of a maxillary lateral incisor using prefabricated titanium and customized zirconia abutments: 4‐year clinical reports - Gerardo Guzman‐Perez (Wiley, 2021)
Abstract The reported clinical scenarios presented two patients, one managed with a prefabricated abutment and the other with a customized abutment, and both patients were pleased with the outcome. However, from a professional viewpoint, the esthetic outcome using the custom zirconia abutment was superior to that using the prefabricated titanium abutment.